The analysis of budget realization in the Indonesian Ministry of Trade before, during and after pandemic of Covid-19 - Ayuntari, Chivalrind Ghanevi; Maharani, Nadira Puspita (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to analyze the effectiveness and efficiency of budget realization at the Indonesian Ministry of Trade on 2017-2022 budget. This research is a quantitative research. Data sources are secondary data and primary data in the form of a Budget Realization Report (LRA) and also in the form of interviews. Data analysis used by calculating the ratio of effectiveness and efficiency and also processing interview data. The result of the study show that the criteria for effectiveness of expenditure realization in 2017-2019 was quite effective, then in period during and after pandemic, shows that the criteria was effective. Efficiency criteria of expenditure realization in the period before pandemic (2017-2019) shows different result. In 2017, the criteria was very efficient, then become quite efficient in 2018, and become efficient in 2019. In the period during and after pandemic, the criteria become efficient.